2006
DOI: 10.1021/ja0615369
|View full text |Cite
|
Sign up to set email alerts
|

An Unprecedented α-Olefin Distribution Arising from a Homogeneous Ethylene Oligomerization Catalyst

Abstract: Treatment of the bis(benzimidazolyl)amine chromium complex 2 with ethylene in the presence of MAO affords an exceptionally active oligomerization catalyst and an unprecedented distribution of 1-olefin products in which the C4n series is much more abundant than the C4n+2 series. Deuterium labeling studies are consistent with a metallacyclic chain growth mechanism in which the unusual product distribution arises from the interplay of two sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 14 publications
2
71
1
1
Order By: Relevance
“…25 We were interested to find out whether this technique can also be applied to higher oligomers and polymers and we have therefore carried out Chromium catalysts 1 and 2 shown in Scheme 2 and related systems have been shown previously to be highly active for the oligomerization of ethylene. 18,[26][27][28] Preliminary cooligomerization experiments employing C 2 H 4 /C 2 D 4 (1:1) with these catalysts have shown that the oligomer fraction consists of even-numbered isotopologues only, which is consistent with a metallacyclic chain growth mechanism. 18 In addition, ethylene/1-nonene cooligomerization experiments with catalyst 1 have shown no incorporation of the higher 1-alkene.…”
Section: Introductionmentioning
confidence: 87%
“…25 We were interested to find out whether this technique can also be applied to higher oligomers and polymers and we have therefore carried out Chromium catalysts 1 and 2 shown in Scheme 2 and related systems have been shown previously to be highly active for the oligomerization of ethylene. 18,[26][27][28] Preliminary cooligomerization experiments employing C 2 H 4 /C 2 D 4 (1:1) with these catalysts have shown that the oligomer fraction consists of even-numbered isotopologues only, which is consistent with a metallacyclic chain growth mechanism. 18 In addition, ethylene/1-nonene cooligomerization experiments with catalyst 1 have shown no incorporation of the higher 1-alkene.…”
Section: Introductionmentioning
confidence: 87%
“…Upon activation with methylaluminoxane (MAO), these pre-catalysts showed high turnover frequencies for ethylene oligomerization under optimized conditions 3 mol C 2 H 4 (mol Cr In parallel, the use of nickel complexes such as NiCl 2 {bis [2-(3,5-dimethyl-1-pyrazolyl)methyl] benzylamine} (3) and NiCl 2 {bis [2-(3,5-dimethyl-1-pyrazolyl)ethyl)]ether} (5) in oligomerization reactions carried out in the presence of triphenylphosphine (PPh 3 ) afforded highly active catalytic systems with turnover frequencies (TOFs) varying from 36. 4 …”
Section: Dois Novos Complexos De Cromo(iii) Contendo Ligantes Tridentmentioning
confidence: 99%
“…Et 2 O, thf and toluene were distilled from sodium-benzophenone ketyl under argon and degassed by freeze-thaw-vacuum cycles prior to use. and [CrCl 3 (thf) 3 ] 10 were prepared by literature procedures. …”
Section: General Proceduresmentioning
confidence: 99%
See 2 more Smart Citations